1992
DOI: 10.1063/1.108134
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of deep level defects in thermally annealed Fe-doped semi-insulating InP by photoinduced current transient spectroscopy

Abstract: Articles you may be interested in Uniformity and physical properties of semi-insulating Fe-doped InP after wafer or ingot annealing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
0

Year Published

1993
1993
2008
2008

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 11 publications
3
12
0
Order By: Relevance
“…We have also reported it in thermally annealed Fe-doped SI InP, and in rapid thermal annealed Fe-doped SI InP. 15,16 Hirt et al have observed, by DLTS, in annealed but still conducting undoped InP, an electron trap having the same activation energy ͑0.4 eV͒ whose concentration increases with phosphorus pressure. 8,10 They as well observe in both undoped and Fe-doped annealed SI InP the same level by TSC.…”
Section: Resultssupporting
confidence: 53%
See 2 more Smart Citations
“…We have also reported it in thermally annealed Fe-doped SI InP, and in rapid thermal annealed Fe-doped SI InP. 15,16 Hirt et al have observed, by DLTS, in annealed but still conducting undoped InP, an electron trap having the same activation energy ͑0.4 eV͒ whose concentration increases with phosphorus pressure. 8,10 They as well observe in both undoped and Fe-doped annealed SI InP the same level by TSC.…”
Section: Resultssupporting
confidence: 53%
“…15 However, it does not appear in thermally annealed Fe-doped SI InP, at 663-820°C temperature for 15 min. 16 Apparently, according to the results obtained in our PICTS studies, two conditions must be satisfied to have A2: presence of iron and annealing under high phosphorus pressure. Hirt et al 10 have observed by TSC a level named T1, having an activation energy of 0.315 eV, for high temperature annealed InP.…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Further annealing of this sample at 700°C for 12 hours causes the 0.65eV peak intensit\( to become stronger than that at 0.66eV and the resistivity decreases to 8.5x104R.cm . The dccrcasc of resistivity of annealed Fe-doped InP is caused by the increase of shallow intrinsic defect conccntration [11,12]. It is interesting that the SI property of this sample is recovered after it is annealed at 800°C and 900°C for about 50 hours.…”
Section: Resultsmentioning
confidence: 99%
“…However, the reproducibility was very poor, which has been associated with the lack of control over the iron concentration and the competition with other contaminants coming from the red phosphorous sources [ 181. Anyway, it is admitted that in the absence of a native deep level, as EL2 in GaAs [19], a minimum iron concentration is required to obtain semi-insulating substrates; below such a concentration, contaminants play an important role in the Compensation [18,20].…”
Section: B Thermal Treatments and Electrical Compensationmentioning
confidence: 99%